Pengelolaan Arsip Dinamis - Zebua, Adiwima; Hutapea, Haposan S. O (Jurnal Mitra Pengabdian Farmasi, 2023)
Universities and private and government institutions are institutions that require archives to store existing archives so that they can be used as information media. is needed again in the framework of the company's needs. Archive management is used as a continuous process that is well planned so that it becomes an archive management that manages records regularly. Then records that have been in the company for a long time may be destroyed because they are no longer valid, but the destruction process must meet the requirements - existing conditions and their destruction must be witnessed by the existing officials.